Pertarungan Politik (Pemilihan Presiden dan Wakil Presiden Indonesia) Dalam Visual Meme - yoni sudiani; eva yanti; cameron malik (Ranah Seni, 2019)
This study discusses the form of political battles that will be held in 2019, which are represented in the form of political memes. As a form of battle, the campaign team from each camp all members involved in the campaign team always have different strategies. For example, the Jokowi-Maaruf team puts forward a defensive strategy, they prefer to explain and clarify all forms of criticism made by the Prabowo-Sandi (PAS) team. Therefore, the visual memes made by Jokowi-Maaruf's team explained more about Jokowi's achievements during his tenure as president which manifest in visual meme that perform in visual communication media such as comics, infographics and posters. Likewise with the Prabowo-Sandi team, the strategies used are more likely to be the style of "attacking" opposing camps, as seen from the many criticisms about the failure of Jokowi's administration during his presidential term. This can be seen from the many visuals meme of scattered in the online community through media as Facebook, Instagram, Twitter and whatsapp groups. This phenomenon shows that the importance of visual meme in political campaign strategies. However, as a campaign strategy, the process of creating visual memes is basically an attempt at framing and branding of each candidate, where each camp can show the advantages and hide the disadvantage of each presidential or vice presidential candidate through visual meme. Visual meme actually tries to simplify complexity of reality, with presenting one side but try to hide the other side.